2015
DOI: 10.1007/s00417-014-2919-5
|View full text |Cite
|
Sign up to set email alerts
|

Venous oxygen saturation is reduced and variable in central retinal vein occlusion

Abstract: Dear Editor;We thank Gokce et al. for their comments on our article about reduced and variable venous oxygen saturation in central retinal vein occlusion (CRVO) [1]. They suggest that environmental chronic cold exposure of our subjects, which is not mentioned in the study, might have affected the results by modifying hematologic and cardiovascular risk factors for CRVO.We would be careful of making any assumptions about the impact of climate on hematological and cardiovascular risk factors in our study populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
1
10
0
2
Order By: Relevance
“…7,8 However, the study also extends these studies by verifying a higher oxygen saturation in retinal arterioles, which was suggested in a previous study but could not be confirmed due to lack of statistical power. 9 The results are also in agreement with findings of increased arterial oxygen saturation in patients with peripheral retinal ischemia secondary to proliferative diabetic retinopathy 14 that correlates with the severity of peripheral retinal ischemia.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…7,8 However, the study also extends these studies by verifying a higher oxygen saturation in retinal arterioles, which was suggested in a previous study but could not be confirmed due to lack of statistical power. 9 The results are also in agreement with findings of increased arterial oxygen saturation in patients with peripheral retinal ischemia secondary to proliferative diabetic retinopathy 14 that correlates with the severity of peripheral retinal ischemia.…”
Section: Discussionsupporting
confidence: 45%
“…5 Retinal ischemia leads to hypoxia in the larger retinal vessels, which can be measured quantitatively by oximetry based on fundus photographs obtained at two different wavelengths. 6 Previous studies have confirmed that the oxygen saturation is reduced in the larger retinal venules in patients with CRVO, 7,8 and that the oxygen saturation improves after treatment of the disease with anti-VEGF medication. 9 However, the relation between visual acuity and retinal oxygen saturation and the predictive value of retinal oxygen saturation for visual outcome in patients with CRVO have not been studied in detail.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…19,20 Therefore, the CFZs beside the first branches may be narrower in order to oxygenate the adjacent retinal tissues. Because changes in the retinal oxygen saturation in retinal vascular disorders have been reported, [21][22][23][24] the CFZs may change. Further studies are needed to elucidate the features of the CFZs.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study by Eliasdottir et al describing reduced venous oxygen saturation in central retinal vein occlusion (CRVO) [1]. The authors proved that oxygen saturation in the retinal venules of eyes with CRVO is significantly reduced.…”
Section: Dear Editor;mentioning
confidence: 96%